2023
DOI: 10.1039/d2tb01701f
|View full text |Cite
|
Sign up to set email alerts
|

Novel metal enhanced dual-mode fluorometric and SERS aptasensor incorporating a heterostructure nanoassembly for ultrasensitive T-2 toxin detection

Abstract: Fluorescent gold (Au) nanostructures have emerged as burgeoning materials to fabricate nanomaterial assemblies with collective tunable plasmon properties and customizable nanoscale architecture which plays a vital role as effective agents...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This configuration exhibited metalenhanced fluorescence (MEF) and enhanced Raman signal amplification. 126 Additionally, Dong et al (2023) investigated bimetallic nanocomposites comprising Au and Ag with SiO 2 shells. This composite structure was designed to enhance fluorescence signals by combining the stability of AuNPs with the enhanced scattering efficiency of Ag, thereby contributing to improved overall performance.…”
Section: Applications Of Nps In Medical and Biotechnological Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration exhibited metalenhanced fluorescence (MEF) and enhanced Raman signal amplification. 126 Additionally, Dong et al (2023) investigated bimetallic nanocomposites comprising Au and Ag with SiO 2 shells. This composite structure was designed to enhance fluorescence signals by combining the stability of AuNPs with the enhanced scattering efficiency of Ag, thereby contributing to improved overall performance.…”
Section: Applications Of Nps In Medical and Biotechnological Fieldsmentioning
confidence: 99%
“…A related study demonstrated the effectiveness of nanostar composites featuring a Au core capped with graphene. This configuration exhibited metal-enhanced fluorescence (MEF) and enhanced Raman signal amplification . Additionally, Dong et al (2023) investigated bimetallic nanocomposites comprising Au and Ag with SiO 2 shells.…”
Section: Applications Of Nps In Medical and Biotechnological Fieldsmentioning
confidence: 99%
“…Furthermore, higher secondary metabolite synthesis and nutrient intake strengthen plants' resistance to plant pathogens. In particular [36], the introduction of silica nanoparticles causes an increase in the plant cell wall thickness and strength in maize (Table 3). It provides an additional layer of defense against predatory insects and the invasion of plant pathogens.…”
Section: Biofertilizer Formulations Using Nanomaterialsmentioning
confidence: 99%
“…When used in situations where they may serve as both a solvent and a reactant, nonaqueous solvents have made possible a novel approach to the production of nanoparticles. The hydrolysis of certain alkoxides can be used on an industrial scale to produce silica and other oxides [36,65]; however, rather than utilizing one reactor, it is more common to use a number of smaller reactors.…”
Section: Production Of Nanoparticles On An Industrial Levelmentioning
confidence: 99%
See 1 more Smart Citation